The Companies Act 1965: Some Recent Amendments - Chan, Wai Meng (Journal of Malaysian and Comparative Law, 2019)
Law is not static. From time to time, it is altered by Parliament as a result of inter alia, changes in circumstances, decisions made by the courts and also to better reflect the intention of the legislature.